This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice one mihar whats your age i did it the same
Multiplying numerator and denominator by 2³, the expression becomes:
(2³+2²)/(2+1)=(8+4)/3=12/3=4, the simplest method I got
2 − 2 + 2 − 3 2 0 + 2 − 1 \ = 4 1 + 8 1 1 + 2 1 = 8 3 1 + 2 1 = 3 2 2 4 = 3 1 2 ∴ 4
Problem Loading...
Note Loading...
Set Loading...
2 − 2 + 2 − 3 2 0 + 2 − 1 = 2 − 2 + 2 − 3 2 2 ( 2 0 − 2 + 2 − 1 − 2 ) = 2 − 2 + 2 − 3 2 2 ( 2 − 2 + 2 − 3 ) = 2 2 = 4